MIRIKIZUMAB – THE EFFICACY OF TREATMENT IN INFLAMMATORY BOWEL DISEASE - Adam Niedziela,; Dominik Domoń,; Dominika Domanowska,; Antoni Liebert,; Natalia Klimek,; Hanna Wilska,; Martyna Kaplińska,; Bartosz Rutka,; Karolina Niewczas,; Adrianna Brzozowska, (International Journal of Innovative Technologies in Social Science, 2025)
Mirikizumab is a humanized monoclonal antibody directed against the p19 subunit of interleukin IL-23. In recent years, it has been the subject of numerous clinical trials as a potential new therapy for inflammatory bowel diseases, including Crohn’s disease and ulcerative colitis. Additionally, mirikizumab has been evaluated in clinical trials as a possible treatment for plaque psoriasis. Clinical trial results in ulcerative colitis led to its approval in the European Union, the United States, Canada, and Japan for the treatment of adult patients with moderately to severely active disease. Despite promising clinical trial outcomes, mirikizumab has not yet been approved for the treatment of Crohn’s disease. This review focuses on summarizing findings from clinical trials investigating mirikizumab in inflammatory bowel diseases. The information is derived from scientific publications indexed in PubMed, searched using the terms “mirikizumab” and “IL-23” and published up to February 2025, as well as from published clinical trial results on mirikizumab.